A New Culinary Culture in Colombia: Equality and Identity in the Interpretation of Traditional Cuisines - Duque-Mahecha, Juliana (ProQuest Dissertations & Theses, 2017)
The broad context of this research is the relation between food and identity and the construction of food networks and critical approaches to food discourses in contemporary settings of food production, distribution and consumption. This project focuses on the study of current food movements and the interpretations of local cuisines from the perspective of main agents involved (chefs, stakeholders, state agents, policy makers, researchers, independent organizations of producers, and consumers) in Colombia. In my analysis of different interpretations of Colombian culinary traditions and the discourses that are weaved from them, not necessarily as part of the same network but rather as part of the same cultural umbrella and national reality, I look at the what to do and how to protect these traditions in the torrent of innovating trends. Cooking responds to this double entendre of a past that is collected, interpreted and then projected on to a present that then overcomes it. New food trends necessarily imply questions about social and cultural equality and identity. That which is novel is exciting and refreshing; it implies learning and broadening boundaries, which are often geographical and social and always cultural. However, the process also entails the inherent challenge to define and answer what is lost and valued in a new scenario and to understand to what purpose. Some categories that have been used to understand such historical processes of cultural production in social systems are class, race, ethnicity and gender, as well as concepts associated with territory, differentiation, integration and democratization, authenticity and exoticization. My purpose in conducting an analytical approach to the development of the gastronomical and culinary subject in Colombia and of building a diagnostic map of it, responds to the wish to contribute to the understanding of the function of food research in solving specific questions of inequality, estrangement, and deracination, as well as understanding new senses of belonging and appropriation that emerge because of urban reconfigurations.